Combined calculation of radiation from large-sized ground RW storage facilities on the basis of Monte Carlo method - Rudychev, V.G.; Azarenkov, N.A.; Girka, I.O.; Rudychev, D.V.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2019)
A technique to reduce the dose rates, produced by large-sized ground-based radiation sources with dozens of radiating elements of the same geometry arranged along the perimeter, is developed. The radiating elements represent the concrete rectangular casks into which cylindrical barrels filled with compacted RW are loaded. The spatial distribution of the radiation around the cask is calculated by the Monte Carlo method. The radiation is assumed to be produced by the definite radionuclides of RW. Shielding by neighboring containers and the presence of an additional biological shielding are taken into account. Different options of the container arrangement are considered. Розроблено методику зменшення дозових навантажень, створюваних приповерхневими джерелами випромінювань великих розмірів, на периметрі яких знаходяться десятки випромінюючих елементів однакової геометрії. Випромінюючі елементи являють собою бетонні прямокутні контейнери, в яких розміщені циліндричні ємності з пресованими РАВ. Виконано розрахунки просторових характеристик випромінювання методом Монте-Карло навколо контейнера, створюваного окремими радіонуклідами РАВ, з урахуванням екранування сусідніми контейнерами при різних варіантах їх розміщення, а також наявності додаткового біозахисту. Разработана методика уменьшения дозовых нагрузок, создаваемых приповерхностными источниками излучений больших размеров, на периметре которых находятся десятки излучающих элементов одинаковой геометрии. Излучающие элементы представляют собой бетонные прямоугольные контейнеры, в которых размещены цилиндрические емкости с прессованными РАО. Выполнены расчеты пространственных характеристик излучения методом Монте-Карло вокруг контейнера, создаваемого отдельными радионуклидами РАО, с учетом экранирования соседними контейнерами при разных вариантах их размещения, а также наличия дополнительной биозащиты.